The influence of ergonomics factors on musculoskeletal disorders (MSDS) in manufacturing company - Amy Shareena, Abd Mubin (2021)
Musculoskeletal disorders (MSDs) has always been related to poor ergonomic application at workplace such as improper posture, repetitive movement, force load activity, poor workplace condition and inadequate workstation design. MSDs not only caused by ergonomics physical factor but including mental perspective. Mental workload is known as occupational stress which contribute to development of MSDs. Reported cases related to occupational musculoskeletal disorders in Malaysia showed increasing trend in the past few years and manufacturing industry contribute the most reported cases. Therefore, the objective of this study is to investigate the influence of ergonomic factors on musculoskeletal disorders among workers in manufacturing company by considering work posture, workstation design and mental workload as the variables. This cross-sectional study is conducted at Auto Parts Manufacturer Sdn. Bhd., in Bukit Beruntung, Selangor. The sample included 200 workers who working in production department. Data is collected using socio-demographic features questionnaire, work posture condition and workstation design questionnaire, NASATLX questionnaire and modified Nordic Musculoskeletal questionnaire. Data is analyzed using SPSS software. Data analysis procedures is being used in this study including descriptive analysis, hypothesis testing, Pearson correlation and multiple regression.